Patient engagement with infection management in secondary care: a qualitative investigation of current experiences - Rawson,T; Moore,L; Hernandez,B; Castro,Sanchez E; Charani,E; Georgiou,P; Ahmad,R; Holmes,A (BMJ Open, 2016)
Objective To understand patient engagement with decision-making for infection management in secondary care and the consequences associated with current practices.Design A qualitative investigation using in-depth focus groups.Participants Fourteen members of the public who had received antimicrobials from secondary care in the preceding 12months in the UK were identified for recruitment. Ten agreed to participate. All participants had experience of infection management in secondary care pathways across a variety of South-East England healthcare institutes. Study findings were subsequently tested through follow-up focus groups with 20 newly recruited citizens.Results Participants reported feelings of disempowerment during episodes of infection in secondary care. Information is communicated in a unilateral manner with individuals ‘told’ that they have an infection and will receive an antimicrobial (often unnamed), leading to loss of ownership, frustration, anxiety and ultimately distancing them from engaging with decision-making. This poor communication drives individuals to seek information from alternative sources, including online, which is associated with concerns over reliability and individualisation. Failures in communication and information provision by clinicians in secondary care influence individuals’ future ideas about infections and their management. This alters their future actions towards antimicrobials and can drive prescription non-adherence and loss to follow-up.Conclusions Current infection management and antimicrobial prescribing practices in secondary care fail to engage patients with the decision-making process. Secondary care physicians must not view infection management episodes as discrete events, but as cumulative experiences which have the potential to shape future patient behaviour and understanding of antimicrobial use.